Disability rates of bus drivers - Raffle, P. A. B. (1974)
Raffle, P. A. B. (1974).British Journal of Industrial Medicine,31, 152-158. Disability rates of bus drivers. The proposal that ordinary driving licences should be valid up to the age of 70 has stimulated much discussion on the place of medical surveillance in the prevention of road crashes. London Transport bus drivers are medically examined on entry to the service, after absence from work attributed to sickness or accident for more than 21 days (and in certain other circumstances), and at age 50 and routinely thereafter. Average annual rates of deaths in the service and recommendations for retiral on medical grounds and for transfers to alternative work for these drivers are presented. These disability rates are low even at the older ages. Most of those drivers who recommended for work other than bus driving were considered to be fit to drive a car. Between ages 50 and 64, 85% of the recommendations for discontinuance of bus driving resulted from post-sickness medical examinations and only 15% from routine age examinations. It is concluded that the available evidence supports the legislative proposals for ordinary driving licensing. However, licence holders will need considerable help from their doctors in discharging their legal obligation to notify their licensing authority of medical conditions likely to affect their ability to drive safely.